The first cross-sectional comparative observational study of sexual dysfunction in Emirati and non-Emirati Parkinson’s disease patients (EmPark-SD) in the United Arab Emirates - Metta, Vinod; Ibrahim, Huzaifa; Qamar, Mubasher A.; Dhamija, Rajinder K.; Popławska-Domaszewicz, Karolina; Benamer, Hani T. S.; Loney, Tom; Mrudula, Rukmini; Falup‑Pecurariu, Cristian; Rodriguez‑Blazquez, Carmen; Dafsari, Haidar S.; Goyal, Vinay; et al. (Scientific reports, 2024)
Sexual dysfunction (SD) is a common non-motor symptom in people with Parkinson’s disease (PD) yet underreported and undertreated specifically in many ethnic PD groups because of religious, social and personal perceptions. We conducted the first single-centre cross-sectional study in the United Arab Emirates of SD in 513 consecutive patients who agreed to complete the survey questionnaires. Data was collected on SD using the Nonmotor Symptoms Scale (NMSS), Index of Erectile Function, and Female Sexual Function Index. Our results show that the non-Emirati group had higher NMSS-SD scores than the Emirati group. SD was reported independent of ethnicity, race and disease stage (p < 0.001). SD correlated with worsening quality of life (p < 0.001) and anxiety domain, especially in young PD patients (p < 0.001). Our data concludes that there is no significant difference in SD between different ethnicity groups, contrary to common perception. SD appears to be underreported in this population and needs addressing using culturally sensitive bespoke counselling.